Proteome‐Wide and Immune Cell Phenotype Mendelian Randomization Highlights Immune Involvement in Genetic Generalized Epilepsy - Jianxiong Gui; Hongyuan Chu; Junjiao Zhang; Xiao Li; Wenwei Liu; Renqiuguo Li; Fan Zhang; Meiyu Dong; Kai Gao; Huaxia Luo; Yuwu Jiang (Brain and Behavior)
ABSTRACT Introduction Genetic generalized epilepsy (GGE) involves polygenic inheritance, with emerging evidence implicating immune mechanisms in seizure pathogenesis. Unlike previous studies focusing on inflammation following seizures, we employed an integrative multi‐omics approach to identify precipitating immune factors in GGE development. Methods Summary data on plasma protein levels were extracted from two large protein quantitative trait loci (pQTLs) studies, measuring 4907 and 2923 plasma proteins in 35,559 and 54,219 individuals, respectively. Immune cell trait data were derived from a genome‐wide association study (GWAS) involving 3757 individuals. GGE data, comprising 7407 cases and 52,538 controls, were sourced from a GWAS meta‐analysis by the International League Against Epilepsy (ILAE). Mendelian randomization (MR) analysis identified associations between plasma proteins, immune cell phenotypes, and GGE. Colocalization analysis assessed whether plasma proteins and GGE share a common causal variant. Transcriptome‐wide association studies (TWAS) from GTEx v8 brain tissue and whole blood were conducted for validation. Drug target prediction and molecular docking identified potential therapeutic interventions. Results We identified 62 potential susceptibility proteins by integrating GWAS data for GGE and its subsyndromes with plasma proteomics data. Of these, eight proteins showed strong evidence of colocalization, primarily within immune‐related pathways. The absolute count of TD CD4+ cells was significantly associated with GGE (OR [95% CI]: 0.69 [0.59, 0.81]). Seven genes (CD46, ITGAM, PRPSAP2, PYDC1, STX4, TMEM106A, and VAT1) were significantly associated with GGE in at least one brain tissue in TWAS analysis. Drug target prediction and molecular docking identified several natural compounds (quercetin, cholecalciferol, resveratrol, curcumin, epigallocatechin gallate, and vitamin E) that may provide ideas for the intervention of GGE. Conclusion These findings revealed causal associations between plasma proteins and GGE, prioritized immune‐related biological pathways, and proposed potential therapeutic hypotheses targeting immunomodulatory mechanisms.